A "space-ball" experiment to specify the nature of gravity in the solar system. (September 2021) - Yefremov, Alexander P.; Vorobyeva, Alexandra A.
Abstract: The high sensitivity of a planet's gravity assist (GA) to changes in test-body impact parameter prompts a space experiment that tests the nature of gravitational fields in the solar system. The Sun, Earth, and Venus can serve as a space-borne laboratory with a primitive space probe ("space ball") as a test body moving on a ballistic trajectory from Earth to Venus, producing GA, and backward to Earth's orbit. We show that in Newton and Einstein (Schwarzschild) gravity, the probe's final positions, which are reached concurrently, may differ markedly, and an Earth-based observer can definitively measure that difference. Highlights: Planet's gravity assist effects on probe trajectories greatly differ for Newton's and Einstein's gravity. Analytical and numerical methods reveal similar effects of gravity law on trajectories. Gravity assist greatly amplifies physical effects faintly changing a probe's orbit. Gravity assist can serve as a space G-lab tool identifying a type of Solar gravity.